Mapping of language brain areas in patients with brain tumors - Hyder, R. (Institute of Electrical and Electronics Engineers Inc., 2015)
Language cortex in the human brain shows high variability among normal individuals and may exhibit a considerable shift from its original position due to tumor growth. Mapping the precise location of language areas is important before surgery to avoid postoperative language deficits. In this paper, the Magnetoencephalography (MEG) recording and the MRI scanning of six brain tumorous subjects are used to localize the language specific areas. MEG recordings were performed during two silent reading tasks; silent word reading and silent picture naming. MEG source imaging is performed using distributed source modeling technique called CLARA ('Classical LORETA Analysis Recursively Applied'). Estimated MEG sources are overlaid on individual MRI of each patient to improve interpretation of MEG source imaging results. The results show successful identification of the essential language areas and clear definition of the time course of neural activation connecting them. Â© 2015 IEEE.